Editorial for the Special Issue on EdTech in Higher Education: Future Perspectives on Teaching and Learning - Janika Leoste; Ugljesa Marjanovic; Branko Andjic (Trends in Higher Education, 2023)
In today’s rapidly evolving world, educational technologies have become indispensable tools for transforming the landscape of higher education [...]